2015
DOI: 10.1111/nph.13627
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association links candidate genes to resistance to Plum Pox Virus in apricot (Prunus armeniaca)

Abstract: SummaryIn fruit tree species, many important traits have been characterized genetically by using single-family descent mapping in progenies segregating for the traits. However, most mapped loci have not been sufficiently resolved to the individual genes due to insufficient progeny sizes for high resolution mapping and the previous lack of whole-genome sequence resources of the study species. To address this problem for Plum Pox Virus (PPV) candidate resistance gene identification in Prunus species, we implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 65 publications
4
57
0
Order By: Relevance
“…The program mlrho was also used to estimate the global sequencing error rate and the nucleotide diversity for each individual separately (see Haubold, Pfaffelhuber, & Lynch, 2010 for the definitions of estimates; Lynch, 2008). The minimum (-m) and maximum (-M) length of reads were fixed at 1 and 100, respectively, with a step (-S) of one (Mariette et al, 2016).…”
Section: Sequencing Error Rate and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The program mlrho was also used to estimate the global sequencing error rate and the nucleotide diversity for each individual separately (see Haubold, Pfaffelhuber, & Lynch, 2010 for the definitions of estimates; Lynch, 2008). The minimum (-m) and maximum (-M) length of reads were fixed at 1 and 100, respectively, with a step (-S) of one (Mariette et al, 2016).…”
Section: Sequencing Error Rate and Diversitymentioning
confidence: 99%
“…How to cite this article: Verdu, C. F., Guichoux, E., Quevauvillers, S., De Thier, O., Laizet, Y., Delcamp, A., Gévaudant, F., Monty, A., Porté, A. J., Lejeune, P., Lassois, L. and Mariette, S. (2016), Dealing with paralogy in RADseq data: in silico detection and single nucleotide polymorphism validation in Robinia pseudoacacia L. Ecology and Evolution, 6: 7323-7333. doi: 10.1002/ece3.2466…”
Section: Data Accessibilitymentioning
confidence: 99%
“…In apricot, the implementation of GWASs for Plum Pox virus (PPV) resistance utilizing NGS platforms to genotype a broad spectrum of the available apricot breeding germplasm verified a previously described single family QTL and specific candidate genes. Thus, demonstrating the utility of the combined approaches of both single family QTL and GWAS studies (Mariette et al, 2016). …”
Section: Genome-wide Tools For Fine Mapping and Dissection Of Traitsmentioning
confidence: 99%
“…AM has been successfully applied in mapping genes involved in several traits in different plant species (maize, sunflower, lettuce, potato, tomato, wheat, etc. ), but only a few studies have been carried out in fruit tree crops, such as peach (Font i Forcada et al, 2013; Micheletti et al, 2015), apple (Cevik et al, 2010), pear (Oraguzie et al, 2010), almond (Font i Forcada et al, 2015a,b), and apricot (Mariette et al, 2016). In almond, these studies have been able to detect the genomic regions where candidate genes involved in the accumulation of important compounds for fruit quality such as tocopherol and phytosterol are located, using the peach reference genome.…”
Section: Genome-wide Tools For Fine Mapping and Dissection Of Traitsmentioning
confidence: 99%
“…Simultaneously, genomics-based crop breeding using NGS technologies is expected to overcome the challenge of feeding an increasing world population. As suggested by Varshney et al (2014), NGS technologies, which have rarely been applied to antiviral breeding using natural variants (Zuriaga et al, 2013; Mariette et al, 2016), would be quite useful for identifying loci in naturally resistant variants and also for breeding to introduce resistant loci into specific cultivars. Several studies have identified loci of interest from Arabidopsis mutants using whole-genome sequencing of pooled mutant F2 populations (Schneeberger et al, 2009; Austin et al, 2011; Uchida et al, 2011).…”
Section: Strategies For Improving the Genetic Resources For Recessivementioning
confidence: 99%